The Influence Of Work-Related Social Media Use (WSMU) And Ethical Leadership On Innovative Work Behavior Mediated By Psychological Well-Being At Gojek Company In South Jakarta - Emilisa, Netania; Febriant, Rizky; Masa, Aurelia Neva; Simarmata, Immanuel Crhyseis Edlyn (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze and explain the influence of Work Related Social Media Use (WSMU) and Ethical Leadership on employees' Innovative Work Behavior, as well as the role of Psychological Well-Being as a mediating variable among Gojek employees in South Jakarta. The study employs a descriptive quantitative approach with a cross-sectional design to examine the effects of Work Related Social Media Use and Ethical Leadership on Innovative Work Behavior, alongside the mediating role of Psychological Well-Being. The unit of analysis consists of Gojek employees in South Jakarta aged between 25 and 40 years. The sample was determined based on the number of questionnaire items (28 questions) with a target of 116 respondents to ensure sufficient analysis and to anticipate incomplete data. Data were collected through questionnaires specifically designed to measure the research variables. Data analysis was conducted in stages, beginning with descriptive statistics using SPSS, followed by testing relationships among variables and mediation using Structural Equation Modeling (SEM) with AMOS. Model fit tests were performed using various fit indices to ensure the validity and strength of the relationships between variables. The results indicate that the four variables interact with each other and have significant positive effects. Both Work Related Social Media Use and Ethical Leadership directly enhance employees’ Psychological Well-Being and Innovative Work Behavior. Moreover, Psychological Well-Being acts as a mediator linking social media use and Ethical Leadership to work innovation. These findings emphasize the importance of Psychological Well-Being as a foundation for employee creativity and productivity. Therefore, companies are advised to optimize professional use of social media and to develop Ethical Leadership to create a psychologically healthy and sustainably innovative work environment.